Psychological characteristics of a fully functioning individual: Rogerian theory - Kilicheva Karomat (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Becoming a fully functioning person is an ongoing process. Humanistic psychology highlights the role of a person in shaping his external and internal world. Carl Rogers believed that humans in their daily lives are creative and active people who stay in the present and are concerned with situations, interpersonal relationships and perceptions, only in the present. Roger’s theory of personality development gives emphasis to human potential and free will for goodness. The objective of this paper is to review and analyze a Rogerian theory of a fully functioning individual.